CARCASS CHARACTERISTICS OF JAPANESE QUAILS (COTURNIX COTURNIX JAPONICA) FED WHOLE OR GROUND PEARL MILLET (PENNISETUM GLAUCUM) WITH OR WITHOUT ENZYME SUPPLEMENTATION - Sabo, M. N.; Duru, S.; Afolayan, S. B. (FUDMA JOURNAL OF SCIENCES, 2020)
An experiment was conducted to evaluate the effect of dietary inclusion level (50% and 100%), form (whole or ground), and enzyme supplementation (with or without) of pearl millet at the expense of maize on the carcass characteristics of growing Japanese quails. Two weeks old unsexed Japanese quails were used in a 2 x 2 x 2 factorial arrangement in a completely randomized design with eight treatments and a control all replicated thrice in a four-week feeding trial. At the end of the 4th week, three quails per treatment were used for carcass evaluation. The quails were fasted, weighed and slaughtered by severing the jugular vein. They were defeathered and eviscerated manually. Weight of the carcass and different parts of the gut were measured using a digital scale and recorded. The results of the study showed that dressing percentage, gizzard weight and liver weight were not affected by dietary inclusion level, form or enzyme supplementation of pearl millet diets. Inclusion of 100% pearl millet, feeding ground pearl millet and pearl millet without enzyme led to increased intestinal weight relative to the control. Quails fed pearl millet without enzyme had heavier proventriculus (0.42T%) than those fed the control (0.35%). Whole and ground pearl millet can conveniently replace maize in the diet of Japanese quails without any adverse effects.